ANALYSIS OF SHEARER SIDE DIRECTION VIBRATION CHARACTERISTICS UNDER DIFFERENT HAULAGE SPEED - MAO Jun; YANG XinWei; WANG DongLiang; SONG QiuShuang (Jixie qiangdu)
According to shearer vibration problems in the practical work,using multi-body dynamics theory,considering shearer support characteristics of guide boots and pin-rail,the friction between flat boots and middle trough,the connection characteristics between the parts of shearer,vibration angle of shearer,6 degrees of freedom dynamic model in the lateral direction of shearer was established. The axial direction of shearer drum load was used as an external excitation,and the effect of different haulage speed on lateral direction vibration characteristics of shearer were solved by using numerical analysis method. The results show that the haulage speed has great influence on vibration displacement of front and rear cutting unit when the range is 2 m/min 5 m/min,the displacement range of front and rear drum is 4. 994 1 mm 11. 262 3 mm、4. 842 0 mm 10. 791 7 mm,and the displacement range of front and rear rocker arm is 3. 199 1 mm 5. 709 7 mm、3. 046 3 mm 5. 236 9 mm. Research results provide the basis for shearer in the actual production process. Finally,the results of model is verified by experiment.